The Experience of a Neurocritical Care Admission and Discharge for Patients and Their Families: A Qualitative Analysis. Issue 4 (August 2020) - Rath, Kelly; Kreitzer, Natalie; Schlichter, Erika; Lopez, Omar; Ferioli, Simona; Ngwenya, Laura B.; Foreman, Brandon
Abstract : ABSTRACT: INTRODUCTION: A qualitative assessment of discharge resource needs is important for developing evidence-based care improvements in neurocritically ill patients. METHODS: We conducted a quality improvement initiative at an academic hospital and included all patients admitted to the neuroscience intensive care unit (ICU) during an 18-month period. Telephone assessments were made at 3 to 6 months after admission. Patients or caregivers were asked whether they had adequate resources upon discharge and whether they had any unanswered questions. The content of responses was reviewed by a neurointensivist and a neurocritical care nurse practitioner. A structured codebook was developed, organized into themes, and applied to the responses. RESULTS: Sixty-one patients or caregivers responded regarding access to resources at discharge with 114 individual codable responses. Responses centered around 5 themes with 23 unique codes: satisfied, needs improvement, dissatisfied, poor post-ICU care, and poor health. The most frequently coded responses were that caregivers believed their loved one had experienced an unclear discharge (n = 11) or premature discharge (n = 12). Two hundred four patients or caregivers responded regarding unanswered questions or additional comments at follow-up, with 516 codable responses. These centered around 6 themes with 26 unique codes: positive experience, negative experience, neutral experience, medical questions, ongoing medical care or concern, or remembrance of time spent in the ICU. The most frequent response was that caregivers or patients stated that they received good care (n = 115). Multiple concerns were brought up, including lack of follow-up after hospitalization (n = 15) and dissatisfaction with post-ICU care (n = 15). CONCLUSIONS: Obtaining qualitative responses after discharge provided insight into the transition from critical care. This could form the basis for an intervention to provide a smoother transition from the ICU to the outpatient setting. Abstract : Supplemental digital content is available in the text.